CREATIVE COLLABORATION IN THE CLASICAL BALLET: MAIN FORMS AND THEIR MANIFESTATION IN THE CREATIVE WORK OF ALEKSANDRS LEMBERGS (Mūzikas akadēmijas raksti, 2024)
The classical dance delivers a message to the spectator, and the only way to do it is the dancer’s full commitment to the process. Nevertheless a routine often takes place and not every performance is creative. The strength of the classical ballet lies in its traditions lasting for centuries, however interaction between the tradition and innovation incited by the dancer’s creative contribution makes the performance attractive and up-to-date. 122 The aim of this article is to analyse the creative collaboration phenomena within the process of the classical ballet acquisition and to reveal the pedagogical conditions for the effective enhancement of the creative collaboration. The main research methods used are cognitive analysis of the philosophical and psychological aspects, analyses of the dancer’s memoirs, reflections of personal experience.